Gender, Race, and Grant Reviews: Translating and Responding to Research Feedback. (January 2020) - Biernat, Monica; Carnes, Molly; Filut, Amarette; Kaatz, Anna
Grant-writing and grant-getting are key to success in many academic disciplines, but research points to gender gaps in both, especially as careers progress. Using a sample of National Institutes of Health (NIH) K-Awardees—Principal Investigators of Mentored Career Development Awards—we examined gender and race effects in response to imagined negative grant reviews that emphasized either promise or inadequacy . Women translated both forms of feedback into worse NIH priority scores than did men and showed reduced motivation to reapply for funding following the review highlighting inadequacy. Translation of feedback mediated the effects of gender on motivation, changing one's research focus, and advice-seeking. Race effects were less consistent, and race did not moderate effects of gender. We suggest that gender bias in grant reviews (i.e., greater likelihood of highlighting inadequacy in reviews of women's grants), along with gender differences in responsiveness to feedback, may contribute to women's underrepresentation in academic medicine.